Evolution of modern education in Ethiopia: A comprehensive review of the historical literature during the imperial periods - Cherinet, Eshetu Mandefro; Mekonen, Abraham Tulu (LPMPP Universitas Negeri Yogyakarta, 2025)
Ethiopia undertakes inordinate opportunities and significant challenges to shape its education system. To fully comprehend Ethiopia's education, it is necessary to understand its history. Thus, this article examines Ethiopian education during the imperial periods, focusing on historical trends, growth patterns, external and internal cultural challenges, and colonial influences that hindered the education transformations. Furthermore, it tries to reflect the bitter truths of imperial governments sacrificed to advance education for nation-building that prudish politicians have covered in the dust in the last decades. It also assesses efforts and support Western partners provide to enhance education in Ethiopia.